Shock ionization in the extended emission-line region of 3C 305: the last piece of the (optical) puzzle - Reynaldi, María Victoria (2013)
We present new Gemini spectroscopical data of the extended emission-line region of the 3C 305 radio galaxy in order to achieve a final answer to the long-standing question about the ionizing mechanism. The spectra show strong kinematic disturbances within the most intense line-emitting region. The relative intensities of the emission lines agree with the hypothesis that the gas is shocked during the interaction of powerful radio jets with the ambient medium. The emission from the recombination region acts as a very effective cooling mechanism, which is supported by the presence of a neutral outflow. However, the observed intensity is almost an order of magnitude lower than expected in a pure shock model. So, autoionizing shock models, in low-density and low-abundance regimes, are required in order to account for the observed emission within the region. This scenario also supports the hypothesis that the optical emitting gas and the X-ray plasma are in pressure balance.